Chapter La signoria nel gioco politico: una lettura strutturale (area subalpina, secoli XIV-XV) - Fiore, Alessio (Reti Medievali E-Book, 2021)
Aim of this article is to discuss the structural role of territorial lordship for its owners in north-western Italy between the fourteenth and fifteenth centuries. Through analysis of a large number of cases, we can see that it performed different functions according to different frameworks. In particular, it was a device for reproducing the social eminence of lords compared to the rest of the regional elite. Indeed, controlling a lordship meant having a huge and stable political capital, which could however be invested in two substantially opposite strategies: in the search for substantial autonomy from state power, or on the contrary in the creation of a structural and symbiotic link with state powers.